First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Flexible and wireless ‘stick-and-detect’ sensor node based on laser-induced graphene for real-time temperature monitoring toward cold chain applications - Hak Jun Lee; Se Eung Ahn; Minhyuk Jung; Hye-ran Moon; Byunghoon Ryu (Chemical Engineering Journal, 2026)

Rocaglamide-A mitigates LPS-induced hepatic inflammation by modulating JNK/AP-1 signaling cascade and ROS production in hepatocytes - Yoon-su Ha; Taek-Kyong Kim; Jun Heo; Jintaek Oh; Seung-Kyoon Kim; Jeongkyu Kim; Jeonghyung Lee; Se-Ran Yang; Seonghwan Hwang; Seung-Jin Kim (Toxicological Research, 2025)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

Zinc Oxide Nanoparticles Exhibit Both Cyclooxygenase- and Lipoxygenase-Mediated Apoptosis in Human Bone Marrow-Derived Mesenchymal Stem Cells - Dong-Yung Kim; Jun-Hyung Kim; Jae-Chul Lee; Moo-Ho Won; Se-Ran Yang; Hyoung-Chun Kim; Myung-Bok Wie (Toxicological Research, 2019)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Insights from 20 years of bacterial genome sequencing - Miriam Land; Loren Hauser; Se-Ran Jun; Intawat Nookaew; Michael R. Leuze; Tae-Hyuk Ahn; Tatiana Karpinets; Ole Lund; Guruprased Kora; Trudy Wassenaar; Suresh Poudel; David W. Ussery (Functional & Integrative Genomics, 2015)

SPARC is involved in the maintenance of mitotically inactivated mouse embryonic fibroblast cells - Jun Yeon Won; Young Jin Lee; Seung-Joon Lee; Woo Jin Kim; Seon-Sook Han; Se-Ran Yang; Heung-Myong Woo; Sung-Min Park; Hyang-Ah Lee; Seok-Ho Hong (In Vitro Cellular & Developmental Biology - Animal, 2013)